A clinical study of peripheral vascular disease due to atherosclerosis in diabetic foot infections - Tyagi, A.; Lavanya, S.; Lavanya, S.; Prasad, G. Hari; Prasad, G. Hari (International Surgery Journal, 2018)
Background: Foot infection is a common problem affecting diabetics. Ischemia is a major factor contributing to progress and morbidity of the disease. The prevalence of peripheral vascular disease is higher in diabetics, with faster progression. The prevalence differs among populations. This study aimed to clinical prevalence of peripheral vascular disease due to atherosclerosis in patients with diabetic foot infections presenting to this tertiary care centre. Methods: This clinical study was conducted in ASRAM hospital, Eluru, Andhra Pradesh, India. All patients admitted with a diagnosis of diabetic foot infection to the department of general surgery during a period between October 2015 to October 2017, who fulfilled the inclusion and exclusion criteria, were enrolled for the study. After recording the pertinent information (as per performa), patients were subjected to a lower limb arterial Doppler and ABPI findings were tabulated. Results: Peripheral vascular disease was found in 35% of patients studied. Majority had distal below the knee vessels stenosis or occlusion. There was significant correlation with age, history of tobacco use and various risk factors. The clinical presentations and outcomes were worse in individuals found to have peripheral vascular compromise on arterial Doppler study. Conclusions: The care of diabetic patients should start with preventive measures which include proper foot care, glycaemic control and education about diabetic foot are key factors for better out come and quality of life.